Aboriginal Peoples Survey 2001 [Canada]: Children off reserve ... : Children off reserve ... - Statistics Canada. Social And Aboriginal Statistics Division (Borealis, 2023)
The 2001 Aboriginal Peoples Survey (APS) was conducted by Statistics Canada to collect data on the lifestyles and living conditions of Aboriginal people in Canada. The survey was designed and implemented in partnership with national Aboriginal organizations. This is the second time the Aboriginal Peoples Survey has been carried out by Statistics Canada; the first time was in the fall of 1991. The data from the 1991 APS were widely used. An extremely important user of the 1991 data was the Royal Commission on Aboriginal Peoples (RCAP). They used the data as a primary source of demographic, social and economic data for their final report and related research studies. The Commission's final report recommended that APS be conducted regularly to monitor the demographic and social conditions of Aboriginal peoples. The federal government responded to the RCAP recommendations through its Aboriginal action plan, Gathering Strength. In this plan the need for relevant and current data was recognized under the umbrella ... : Notes: The PUMF covers the off-reserve child Aboriginal population only, that is, children living either on- or off-community, but not in a First Nation community or reserve; ...